Molecular docking of sterol derivatives in Tagetes erecta Linn. as an antiatherosclerotic agents through activation of PPARÎ³ and LXRÎ± receptors - I Wayan Surya Rahadi; Ni Kadek Ayu Mas Ratnadewi; Ketut Agus Adrianta (Pascasarjana Universitas Negeri Medan, 2024)
Atherosclerosis is a condition characterized by inflammation in the arteries, which is linked with the accumulation of lipids and alterations in metabolism. Considering that atherosclerosis is the main factor causing death in the world, it is necessary to carry out immediate prevention and treatment to reduce the risk of developing clinical severity. The creation of foam cells, which originate from macrophages, is considered a key element in cardiovascular ailments, particularly in the advancement of atherosclerosis. Two types of the nuclear receptors known as Peroxisome proliferator-activated receptor Î³ (PPARÎ³) and liver X receptor Î± (LXRÎ±), which serve as a primary regulator of cholesterol, intracellular lipid homeostasis and they are instrumental in the process of reverse cholesterol transport (RCT). Activation of these receptors could potentially decrease foam cell formation, consequently lowering the risk of atherogenesis and reducing cardiovascular disease risk. This research aims to determine sterol derivative compounds in Tagetes erecta Linn. which have the best interaction and potential as anti-atherosclerosis through peroxisome proliferator-activated receptor Î³ (PPARÎ³) and liver X receptor Î± (LXRÎ±) activation. The analysis of this study is using docking molecular analysis. The parameters observed in this study were docking score, visualization results, absorption, distribution, metabolism, excretion profile, and toxicity value. The molecular docking outcomes indicate that Î²-sitosterol and 7Î²-hydroxysitosterol possess the most favorable binding energy values. They exhibit a positive pharmacokinetic profile, with the exception of gastrointestinal absorption and respiratory toxicity.